Determinants of ISPA Incidents in Toddlers in the Working Area of Pangkalan Budiman Community Health Center, Serdang Bedagai Regency in 2022 - Perangin-Angin, Susanti Br; Richard Jerry (PT FORMOSA CENDEKIA GLOBAL, 2024)
ISPA is an acute respiratory infection caused by bacteria or viruses, with ISPA sufferers typically experiencing symptoms for 14 days. Based on the research results, it can be concluded that there are four variables related to the frequency of ISPA, namely: humidity with a value p=0.000 (p<0.05), lighting with a value p=0.49 ( p<0).05), smoking behavior at home with a value p=0.018 (p<0.05) and window opening behavior with a value p=0.005 (p<0.05) and there is only one variable that is not related to the incidence of ARF, namely ventilation with p-value = 0.414 (p>0.05)